(untitled) (Journal of actual problems of jurisprudence, 2019)
Given article it is devoted legal status of the suspect on criminally-procedural right Republics Kazakhstans and to their right to protection, a role of the lawyer-defender in maintenance of legal protection of their rights and freedom, both at a stage of preliminary investigation, and at a stage of the main proceeding.